2005
DOI: 10.1364/ao.44.000103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of multiple pulse nonlinear optoacoustic signal generation and control

Abstract: Generating underwater acoustic signals from a remote, aerial location by use of a high-energy pulsed infrared laser has been demonstrated. The laser beam is directed from the air and focused onto the water surface, where the optical energy was converted into a propagating acoustic wave. Sound pressure levels of 185 dB re microPa (decibel re microPa) were consistently recorded under freshwater laboratory conditions at laser-pulse repetition rates of up to 1000 pulses/s. The nonlinear optoacoustic transmission c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…[4][5][6] It has been recognized early on that an intense laser pulse focused in a transparent liquid can heat or ionize the medium, leading to the emission of an acoustic transient. 7,8 A laser-based method offers advantages in standoff underwater acoustics in comparison with traditional sources consisting of arrays of hydro-acoustic transducers or sonars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] It has been recognized early on that an intense laser pulse focused in a transparent liquid can heat or ionize the medium, leading to the emission of an acoustic transient. 7,8 A laser-based method offers advantages in standoff underwater acoustics in comparison with traditional sources consisting of arrays of hydro-acoustic transducers or sonars.…”
Section: Introductionmentioning
confidence: 99%
“…100k where k is the acoustic wavelength defined by k ¼ water /F us , where F us is the ultrasound frequency and water the speed of sound in water with water % 1487 m/s at T ¼ 21. 6 C. They could be moved longitudinally and collinearly with respect to the laser propagation axis using a motorized platform. The experimental setup is sketched in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several transients associated with the single opto-acoustic transmission pulse are clearly visible. Therefore, a nonlinear opto-acoustic conversion is generated each time, and three to four additional transient oscillations following the optical breakdown transient are created [8]. The first transient is related to the initial optical breakdown of the water molecules due to the high-energy density and intensity of the laser pulse at the focal point in the water, which produces an acoustic shock wave.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional sonar is limited to detecting the little targets because of its relatively lower resolution compared with laser acoustic sources generated by LIB. Therefore, as an alternative approach, laser acoustic sources have such advantages as, first, laser acoustic sources can be generated far away from air to water in the flexible aerial platform, that is, this method employs a non-contact, covert, optical method to provide greatly enhanced communications and remote active transmission capabilities [8], second, these pulsed sources are of narrow duration, wide and tunable frequency spectrum, and extensive applications [9], and the third, the efficiency of opto-acoustic conversion is up to 30% [10]. It is of importance to study the characteristics of the LIB comprehensively, especially the directivity of sound field for such practical applications as selection of LIB conditions and design of the signal reception system in ocean exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results in [4] have shown that the SPL for a linear optoacoustic process yields up to 140 dB re 1 µPa. Meanwhile, the SPL of a nonlinear optoacoustic effect is as high as 185.61 dB re µPa at 1 m, and over 210 dB re µPa at 1 m have been reported in [5] and [6], respectively.…”
Section: Introductionmentioning
confidence: 99%